Insights into the genome architecture and evolution of Shiga toxin encoding bacteriophages of Escherichia coli - Pinto, Graça (2021)
Background: A total of 179 Shiga toxin-producing Escherichia coli (STEC) complete genomes were analyzed in terms of serotypes, prophage coding regions, and stx gene variants and their distribution. We further examined the genetic diversity of Stx-converting phage genomes (Stx phages), focusing on the lysis-lysogeny decision and lytic cassettes. Results: We show that most STEC isolates belong to non-O157 serotypes (73 %), regardless the sources and geographical regions. While the majority of STEC genomes contain a single stx gene (61 %), strains containing two (35 %), three (3 %) and four (1 %) stx genes were also found, being stx2 the most prevalent gene variant. Their location is exclusively found in intact prophage regions, indicating that they are phage-borne. We further demonstrate that Stx phages can be grouped into four clusters (A, B, C and D), three subclusters (A1, A2 and A3) and one singleton, based on their shared gene content. This cluster distribution is in good agreement with their predicted virion morphologies. Stx phage genomes are highly diverse with a vast number of 1,838 gene phamilies (phams) of related sequences (of which 677 are orphams i.e. unique genes) and, although having high mosaicism, they are generally organized into three major transcripts. While the mechanisms that guide lysis–lysogeny decision are complex, there is a strong selective pressure to maintain the stx genes location close to the lytic cassette composed of predicted SAR-endolysin and pin-holin lytic proteins. The evolution of STEC Stx phages seems to be strongly related to acquiring genetic material, probably from horizontal gene transfer events. Conclusions: This work provides novel insights on the genetic structure of Stx phages, showing a high genetic diversity throughout the genomes, where the various lysis-lysogeny regulatory systems are in contrast with an uncommon, but conserved, lytic system always adjacent to stx genes.